Essensial Oil Difusser Lavender Terhadap Pengurangan Morning Sickness Pada Ibu Hamil Trimester 1: Lavender Essential Oil Difusser Against Reduction of Morning Sickness in First Trimester Pregnant Women - Muzayyana; Alhidayah; Sitti Nurul Hikma Saleh; St. Rahmawati Hamzah; Agustin; Suci Rahayu Ningsih (Institut Teknologi Kesehatan dan Bisnis Graha Ananda, 2023)
Nausea and vomiting in pregnancy is generally called morning sickness, experienced by around 70-80% of pregnant women and is a phenomenon that often occurs at 5-12 weeks of gestation. One of the treatments to reduce non-pharmacological therapy is giving lavender aromatherapy. The aim of this research is to determine the effect of giving lavender aromatherapy to reduce vomiting and nausea in first trimester pregnant women. This type of research uses quantitative research with a Pre-Experimental Design approach in the form of One Group Pre-test and Post-test. The population in this study were pregnant women in the first trimester who experienced morning sickness. Sample technique with purposive sampling. Bivariate analysis using the Dependent t test. The results of this study showed that there was a significant reduction in nausea and vomiting in the intervention group after administering lavender aromatherapy as evidenced by the T test p-value = 0.000 (p-value < 0.05). Providing lavender aromatherapy can be used to reduce nausea and vomiting in pregnant women as an effective non-pharmacological therapy